Heat transfer experimental and numerical study of a three-sided serpentine with the operating fluid directly contacting the PV cell back - Barbosa, F.; Nobrega, G.; Souza, R. R.; Ralha, R. P.; Cardoso, E. M. [UNESP]; Pereira, J. E.; Afonso, I. S.; Marques, F.; Teixeira, J. C.F.; Lima, R.; Moita, A. S. (Elsevier, 2024)
The cooling methodologies of photovoltaic/thermal equipment are crucial not only to maintain optimal operating temperatures but also to improve the performance of the photovoltaic systems and prolong their lifespan. Traditional heat exchangers often require physical contact with the material to be cooled, posing challenges for specific projects. Therefore, this study introduces an innovative heat exchanger made of aluminum plate, allowing direct contact of the cooling liquid with the surface to be cooled. The thermal performance of the serpentine, coupled to a steel plate simulating a photovoltaic-thermal panel, was evaluated experimentally. CFD numerical simulations were conducted to analyze the thermal performance of the heat exchanger, providing valuable temperature profiles for single-phase flows. The outcomes showed that the simulated and experimental data agreed well. Particularly, when considering the outlet fluid temperature the mean absolute error between the simulated and experimental results was around 0.5 °C, with a relative error of aproximatelly 1.8 %. To evaluate the influence of the type of material that forms the serpentine, heat exchangers with two different polydimethylsiloxane (PDMS) serpentines were numerically investigated. The PDMS serpentine provided a more heterogeneous steel plate temperature profile compared to the aluminum one; however, such an issue can be corrected with geometry modifications, such as a greater width and cross-sectional area. For all flow rates, the steel plate temperature using aluminum serpentine presented a lower average temperature than that with PDMS serpentine (an average of 6.3 % lower). The wide PDMS serpentine exhibited a better cooling performance than the narrow PDMS serpentine (an average of 92 %) since the heat transfer surface area was enhanced in the former case.
Keywords: Aluminum serpentine; Cooling performance; Energy analysis; Heat sink materials; PDMS serpentine; Photovoltaic system